2003
DOI: 10.1038/sj.bjp.0705293
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dobesilate potentiates endothelium‐derived hyperpolarizing factor‐mediated relaxation of human penile resistance arteries

Abstract: 1 We have evaluated the participation of endothelium-derived hyperpolarizing factor (EDHF) in the endothelium-dependent relaxation of isolated human penile resistance arteries (HPRA) and human corpus cavernosum (HCC) strips. In addition, the effect of the angioprotective agent, calcium dobesilate (DOBE), on the endothelium-dependent relaxation of these tissues was investigated. 2 Combined inhibition of nitric oxide synthase (NOS) and cyclooxygenase (COX) nearly abolished the endothelium-dependent relaxation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…Functional differences between HPRA and HCC in response to vasoactive drugs have been previously described (Hedlund and Andersson, 1985;Angulo et al, 2002). In addition, endotheliumdependent relaxation attributed to endothelium-derived hyperpolarizing factor plays a significant role in human penile arteries but not in corpus cavernosum (Angulo et al, 2003). This endothelial process involving KCa, which is functional in penile arteries but not in trabecular tissue, is a functional divergence that could be related to the present findings.…”
Section: Figuresupporting
confidence: 52%
See 1 more Smart Citation
“…Functional differences between HPRA and HCC in response to vasoactive drugs have been previously described (Hedlund and Andersson, 1985;Angulo et al, 2002). In addition, endotheliumdependent relaxation attributed to endothelium-derived hyperpolarizing factor plays a significant role in human penile arteries but not in corpus cavernosum (Angulo et al, 2003). This endothelial process involving KCa, which is functional in penile arteries but not in trabecular tissue, is a functional divergence that could be related to the present findings.…”
Section: Figuresupporting
confidence: 52%
“…Activators of KCa also have the capacity to relax human and animal penile smooth muscles Hewawasam et al, 2004). In addition, this type of channels has a key role in endothelium-derived hyperpolarizing factor-mediated relaxation of human penile arteries (Angulo et al, 2003). Furthermore, the delivery of the gene for human BK (hSlo) into the penis has been shown to increase erectile responses in aged rats (Melman et al, 2003) and to recover erectile function in diabetic rats (Christ et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, the endothelium exerts regulatory effects on vasodilatation, as it releases numerous vasoactive substances, such as NO, bradykinin, prostaglandin I2, substance P and so on. EDHF is another vasoactive substance and it has been found in rat, horse and human penile small arteries [5][6][7][8]17]. Moreover, in systemic arteries, several EDHF candidates have been suggested, including potassium ions, products of the cytochrome P450 pathway, C-type natriuretic peptide, hydrogen peroxide and K + [7,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-established nitric oxide (NO)/ cyclic guanosine monophosphate pathway, recent reports have shown the existence of a second, distinct endothelial pathway involving the endothelium-dependent hyperpolarization factor (EDHF). Specifically, this factor has been shown to be involved in the relaxation of the vascular smooth muscle cells in penile arteries [5][6][7][8]. Angulo [9] has reported that diabetes can impair endothelium-dependent relaxation of human penile vascular tissues mediated by EDHF, but the causes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…60,61 However, the involvement of endothelial NO in the agonist-induced vasodilations of the erectile tissues is variable, being more relevant in CC 17,31,60,82 than in the small penile resistance arteries, where a non-NO non-prostanoid factor is a major component of the endothelium-dependent relaxant responses. 60,61,83,84 Clinical investigations have recently demonstrated a flow-dependent vasodilatation in penile arteries by measuring the changes in the cavernous artery diameter after 5 min occlusion of penile flow. 85 These studies showed that flow-induced vasodilatation is strongly impaired in patients with organic ED and proposed this measurement as a clinical test to evaluate penile endothelial function.…”
Section: Prostanoidsmentioning
confidence: 99%